2012
DOI: 10.1111/j.1469-8137.2012.04157.x
|View full text |Cite
|
Sign up to set email alerts
|

Glasshouse vs field experiments: do they yield ecologically similar results for assessing N impacts on peat mosses?

Abstract: Summary• Peat bogs have accumulated more atmospheric carbon (C) than any other terrestrial ecosystem today. Most of this C is associated with peat moss (Sphagnum) litter. Atmospheric nitrogen (N) deposition can decrease Sphagnum production, compromising the C sequestration capacity of peat bogs. The mechanisms underlying the reduced production are uncertain, necessitating multifactorial experiments.• We investigated whether glasshouse experiments are reliable proxies for field experiments for assessing interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Our results also seem to contradict findings by Taylor and Dhileepan (2012) who observed that LP had higher growth rates than SP in the field. These differences could be attributable to environmental (Evans and Hughes 1961) and growing conditions (field vs glasshouse) (Limpens et al 2012). Moreover, whilst we generated experimental plants from seeds (seedlings) in our experiments, Taylor and Dhileepan (2012) used plants grown from tuberlings.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also seem to contradict findings by Taylor and Dhileepan (2012) who observed that LP had higher growth rates than SP in the field. These differences could be attributable to environmental (Evans and Hughes 1961) and growing conditions (field vs glasshouse) (Limpens et al 2012). Moreover, whilst we generated experimental plants from seeds (seedlings) in our experiments, Taylor and Dhileepan (2012) used plants grown from tuberlings.…”
Section: Discussionmentioning
confidence: 99%
“…These use multiple view imaging systems including thermal sensors, together with automated plant handling under controlled environment conditions to quantify plant growth and function. However, genetic analysis and breeding for most crop species is usually carried out under natural conditions because results from glasshouse trials do not always correlate well with field behaviour [7], [8], [9], [10]. Phenotyping in field trials is therefore likely to provide better insights into crop behaviour than studies under glasshouse conditions, especially for crops such as potato that have large canopy size and show restricted growth in pots [11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, warming and more frequent heat waves (Meehl & Tebaldi, 2004) can increase water deficits, evapotranspiration, and HWT (Clair, 1998;Zona et al, 2011) resulting in drought stress for Sphagnum (Bragazza, 2008). High nitrogen input can inhibit Sphagnum growth (Berendse et al, 2001;Limpens et al, 2012) but increase population expansion (Bubier et al 2007;Bu et al, 2011). The stepwise regression shows a negative effect of lowered water table in S. palustre, but the effect seems too small to suggest an advantage for the other mosses if climate change leads Table 3 Stepwise regression analyses for the relationships between biomass growth (g) of the four species and environmental factors.…”
Section: Discussionmentioning
confidence: 99%